The Measurement of Regional Government Financial Performance Using the Value for Money Principle - Shidqi, Alfi Irsyad; Murdiansyah, Isnan (Gorontalo Accounting Journal, 2024)
The purpose of this study is to determine and analyze the financial performance of the local government of Banyuwangi Regency using the concept of value for money at the Regional Financial and Asset Management Agency of Banyuwangi Regency. The method used is descriptive qualitative, with primary and secondary data. Data analysis techniques use the concept of value for money with economic, efficient, and effective ratios. The results of this study state that the Banyuwangi Regency Government, through economic, efficiency, and effectiveness ratios in budget realization reports in the 2019-2022 period fully applies the principle of value for money.